2020
DOI: 10.3390/jmse8080587
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Suction Stabilized Floating Platforms

Abstract: The occurrence of parametric resonance due to the time varying behavior of ocean waves could lead to catastrophic damages to offshore structures. A stable structure that could withstand the wave perturbations is quintessential to operate in such a harsh environment. In this work, the authors detail the relevance of a Suction Stabilized Float (SSF) or a Suction Stabilized Floating platform towards such an application. A generic design of a symmetrically shaped float structure along with its inherent stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In this section, a brief outline of the Floquet theory and Normal Forms theory is provided along with a proposed approach. A detailed explanation of these theories and the proposed approach are provided in the prior work [20].…”
Section: Mathematical Background and Methodologymentioning
confidence: 99%
“…In this section, a brief outline of the Floquet theory and Normal Forms theory is provided along with a proposed approach. A detailed explanation of these theories and the proposed approach are provided in the prior work [20].…”
Section: Mathematical Background and Methodologymentioning
confidence: 99%
“…Recently, the authors have demonstrated the computation of the closed-form expression for the Lyapunov–Floquet (L-F) transformation matrix and stability analysis for a time periodic system, using the normal form and state augmentation techniques in Subramanian and Redkar (2020), Subramanian et al (2020). They have also applied similar approach toward the analysis and control of attitude motion of spacecrafts and reduction of nonlinear systems using the center manifold technique in Waswa and Redkar (2020a), Waswa et al (2020).…”
Section: Introductionmentioning
confidence: 99%